A New Arylsulfate Sulfotransferase Involved in Liponucleoside Antibiotic Biosynthesis in Streptomycetes - Kaysser, Leonard; Eitel, Kornelia; Tanino, Tetsuya; Siebenberg, Stefanie; Matsuda, Akira; Ichikawa, Satoshi; Gust, Bertolt (The Journal of biological chemistry, 2010)
Sulfotransferases are involved in a variety of physiological processes and typically use 3′-phosphoadenosine 5′-phosphosulfate (PAPS) as the sulfate donor substrate. In contrast, microbial arylsulfate sulfotransferases (ASSTs) are PAPS-independent and utilize arylsulfates as sulfate donors. Yet, their genuine acceptor substrates are unknown. In this study we demonstrate that Cpz4 from Streptomyces sp. MK730–62F2 is an ASST-type sulfotransferase responsible for the formation of sulfated liponucleoside antibiotics. Gene deletion mutants showed that cpz4 is required for the production of sulfated caprazamycin derivatives. Cloning, overproduction, and purification of Cpz4 resulted in a 58-kDa soluble protein. The enzyme catalyzed the transfer of a sulfate group from p-nitrophenol sulfate (Km 48.1 μm, kcat 0.14 s−1) and methyl umbelliferone sulfate (Km 34.5 μm, kcat 0.15 s−1) onto phenol (Km 25.9 and 29.7 mm, respectively). The Cpz4 reaction proceeds by a ping pong bi-bi mechanism. Several structural analogs of intermediates of the caprazamycin biosynthetic pathway were synthesized and tested as substrates of Cpz4. Des-N-methyl-acyl-caprazol was converted with highest efficiency 100 times faster than phenol. The fatty acyl side chain and the uridyl moiety seem to be important for substrate recognition by Cpz4. Liponucleosides, partially purified from various mutant strains, were readily sulfated by Cpz4 using p-nitrophenol sulfate. No product formation could be observed with PAPS as the donor substrate. Sequence homology of Cpz4 to the previously examined ASSTs is low. However, numerous orthologs are encoded in microbial genomes and represent interesting subjects for future investigations.